EXPLORING WRITING STRATEGIES OF BILINGUAL STUDENTS - Romadhon Romadhon; Edy Waloyo (IAIN Syekh Nurjati Cirebon, 2020)
Scholars have long debated the impact of bilingualism on foreign language acquisition. This research was conducted in Senior High School and it involved five bilingual students. They were considered qualified as research subjects because of their language background. The researchers employed observation, documentation of students’ writing, and in-depth interview to gain the data. The aims of this research are: to describe the bilingual students’ writing performance, to explore writing strategies used by bilingual students, and the reasons why they use those strategies. The research findings suggest that students had a lack of awareness in the organization and content of their writing because they were only concerned about the structure and spelling. Bilingual students used some strategies during writing preparation, while writing, and revision. During the writing preparation, they preferred to write carefully and collaboratively by making a draft, writing scratch before real writing, asking teacher's instruction, and others. While writing, they did not really give attention to readers’ perspectives. Also during the revision process, they were concerned to edit words or sentences instead of revising the content or organization.